Adenosine deficiency facilitates CA1 synaptic hyperexcitability in the presymptomatic phase of a knockin mouse model of Alzheimer disease - Mattia Bonzanni; Alice Braga; Takashi Saito; Takaomi C. Saido; Giuseppina Tesco; Philip G. Haydon (iScience)
Summary: The disease’s trajectory of Alzheimer disease (AD) is associated with and negatively correlated to hippocampal hyperexcitability. Here, we show that during the asymptomatic stage in a knockin (KI) mouse model of Alzheimer disease (APPNL−G-F/NL−G-F; APPKI), hippocampal hyperactivity occurs at the synaptic compartment, propagates to the soma, and is manifesting at low frequencies of stimulation. We show that this aberrant excitability is associated with a deficient adenosine tone, an inhibitory neuromodulator, driven by reduced levels of CD39/73 enzymes, responsible for the extracellular ATP-to-adenosine conversion. Both pharmacologic (adenosine kinase inhibitor) and non-pharmacologic (ketogenic diet) restorations of the adenosine tone successfully normalize hippocampal neuronal activity. Our results demonstrated that neuronal hyperexcitability during the asymptomatic stage of a KI model of Alzheimer disease originated at the synaptic compartment and is associated with adenosine deficient tone. These results extend our comprehension of the hippocampal vulnerability associated with the asymptomatic stage of Alzheimer disease.